MicroRNA as tools and therapeutics in lung cancer - Barger, Jennifer F (Respir Med, 2015)
Lung cancer is the number one cause of cancer related deaths. The lack of specific and accurate tools for early diagnosis and minimal targeted therapeutics both contribute to poor outcomes. The recent discovery of microRNAs (miRNAs) revealed a novel mechanism for post-transcriptional regulation in cancer and has created new opportunities for the development of diagnostics, prognostics and targeted therapeutics. In lung cancer, miRNA expression profiles distinguish histological subtypes, predict chemotherapeutic response and are associated with prognosis, metastasis and survival. Furthermore, miRNAs circulate in body fluids and hence may serve as important biomarkers for early diagnosis or stratify patients for personalized therapeutic strategies. Here, we provide an overview of the miRNAs implicated in lung cancer, with an emphasis on their clinical utility.